Impact of carbon emission difference on the dual-channel fresh produce supply chain with capital constraints - Bai, Shizhen; Jia, Xuelian (Frontiers in Environmental Science, 2023)
The difference in carbon emissions has an important impact on the decision-making of dual-channel fresh produce supply chain financing. We set up a Stackelberg game model of a dual-channel supply chain under the financing strategy of banks and retailers to study the optimal operation decision and financing strategy selection. Our analysis results show that when the retailer’s interest rate and the carbon emission difference met certain conditions, the supplier always chooses the financing strategy of retailers.